ANALISIS KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) BERAS CERDAS CV AN – NAHLAH DI KABUPATEN JEMBER - Anggraini Dwi Rahayu; Triana Dewi Hapsari; Julian Adam (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
This study was aimed to identify : (1) consumer characteristic related to their willingness to pay for beras cerdas CV An – Nahlah in Jember ; (2) maximum average willingness to pay of beras cerdas CV An – Nahlah consumer in Jember ; (3) factors affecting consumer willingness to pay for beras cerdas CV An – Nahlah in Jember. The method used is analytical descriptive method. Sample taken purposively using incidental sampling technique. The data analyzed using descriptive analysis and multiple linier regression. The study showed that (1) the characteristics of beras cerdas CV An – Nahlah consumer was related to their willingness to pay are; female, has a bachelor degree, include in adult group, married employed, average income Rp 1.500.000 – Rp 3.000.000 monthly their willingness to pay ranged between Rp 17.001 – Rp 21.000 per 800 gram. (2) maximum average consumer willingness to pay is Rp 20.075 per 800 gram. (3) factors influenced consumer willingness to pay are; age, gender, married status, education, job, and monthly income.